GAS EXCHANGE IN ‘POME’ BANANA PLANTS GROWN UNDER DIFFERENT IRRIGATION SYSTEMS - Arantes,Alessandro de M. (2018)
Abstract This study aimed to evaluate Pome type bananas grown under different irrigation systems. Seventy-two treatments were used in a factorial 3×2×12 scheme, where factors consisted of three irrigation systems (under-tree sprinkling, micro-sprinkling, and dripping), two cultivars (‘Prata-Anã‘ and ‘BRS Platina’), and twelve evaluation periods (months). The treatments were arranged in a completely randomized design with five repetitions. During the third production cycle, plant phytotechnical and physiological traits were evaluated in different months at five different times of the day. The results showed no significant interactions between cultivars and irrigation systems. All the assessed traits varied for each irrigation system, except for plant yield. The banana plants presented higher vigor and a larger number of hands when grown under conventional sprinkling and micro-aspersion systems, regardless of the cultivar. The cultivar ‘Prata-Anã‘ has larger leaf areas and number of hands, regardless of the irrigation system. Moreover, plants irrigated by dripping exhibited higher leaf temperatures, higher transpiration rates, and lower instant water-use efficiency. When irrigated by micro-sprinklers, the plants displayed greater water-use efficiency. As leaf temperature rose, perspiration increased linearly, while the instant water-use efficiency decreased linearly.